Menguji Peran Pembiayaan Mudharabah, Musyarakah, dan Murabahah Dalam Peta Profit Efficiency Perbankan Syariah di Indonesia Masa Pandemi COVID-19 - Saparuddin Siregar; Sugianto Sugianto; Syachrul Wahyudi (Jurnal Ilmiah Ekonomi Islam, 2022)
Sharia banking in Indonesia is currently facing a big challenge, COVID-19, which has made the country's economy and society sluggish. This study aims to examine the roles of murabahah, mudharabah, and musyarakah financing in the profit efficiency map of Islamic banking in Indonesia in the period before and during the COVID-19 pandemic. The sample data used is monthly aggregate data from Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) for the period January 2018 – August 2021. The Stochastic Frontier Analysis (SFA) method is used in this study to estimate profit efficiency and the determinant factors involved. The results of this study indicate the estimated average value of profit efficiency is 85.83%. The value of profit efficiency during the COVID-19 pandemic is relatively greater than before the pandemic. BUS has a relatively smaller profit efficiency than UUS in the before and during pandemic period. Mudharabah financing become significant determinant factors on profit efficiency. On the contrary musyarakah financing has negatif effect, and murabahah has not yet taken a significant role as a determinant factor during the sample period.